Book Review of Strangers to Ourselves: Unsettled Minds and the Stories That Make Us - Strong, Tom (Canadian Journal of Counselling and Psychotherapy, 2024)
Rachel Aviv, a staff writer at The New Yorker, explores the roles and inadequacies of stories in accounting for and shaping the lives of people “unsettled” by crisis and mental distress. Through six evocative case examples, including her own experience of being diagnosed with anorexia at age 6, she highlights the complexities and centrality of narrative meaning making by clients and professionals when they address mental health concerns. Such stories made out of distress not only implicate the identities of clients and professionals but also change with different medical and cultural developments. This is a book that will interest and perhaps perplex counsellors who have embraced narrative ideas and practices.